Effect of Social Cognitive Therapy on Mental Improvement in Post Traumatic Stress Disorder: A Meta-Analysis - Yovita Galuh Eka Ariska; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Post Traumatic Stress Disorder (PTSD) is a mental disorder that develops after experiencing a very threatening or horrific event. Cognitive behavioral therapy or Cognitive Behavior Therapy (CBT) is one of the most popular therapies. The purpose of this study was to analyze the effect of cognitive behavioral therapy on mental improvement in Post Traumatic Stress Disorder patients. Subjects and Method: This study is a systematic review and Meta-analysis using PICO model. Population: Post Traumatic Stress Disorder patients. Intervention: cognitive behavioral therapy. Comparison: no cognitive behavioral therapy. Outcome: Mental Improvement. The online databases used are Google Scholar, PubMed, and Sience Direct with keywords (“Post Traumatic Stress Disorder” OR “PTSD”) AND (“Cognitive Behavioral Therapy” OR “Cognitive Behavioral Therapy” OR “CBT”) AND (“Randomized controlled trial” OR “RCT”). There were 9 randomized controlled trial studies published in 2005-2023 that met the inclusion criteria. Analysis was performed using RevMan 5.3. Results: A Meta-analysis conducted using 9 RCTs from the United States, Australia, the Netherlands, Sweden, and Thailand. A total sample was 6,088 health workers. Cognitive behavioral therapy reduced PTSD (SMD= -6.32; p= 0.020). Forest plots showed high heterogeneity (I2=73%; p= 0.003), so analysis was conducted using the random effect model. Conclusion: CBT reduces PTSD. Keywords: cognitive behavior therapy, mental improvement, post-traumatic stress disorder, randomized controlled trial